AN INDONESIA-FRANCE COMPARISON: THE DESIGN MECHANISM FOR LEGISLATION ESTABLISHMENT AND LEGISLATION REGULATION EVALUATION - Arlinandes Chandra, Jeffri; Wahanisa, Rofi; Kosasih, Ade; Bararah Barid, Vera (jfpublisher, 2022)
The good laws and regulations are in harmony with other laws and regulations. The disharmony of a statutory regulation with other regulations, both at the same level and at different levels, will cause a complex problem. As a result, these regulations can be canceled due to things that are contrary to constitution, laws and other regulations. This research is a qualitative research. The research method used is a combination of normative research supported by empirical field research data, namely research that uses information from research targets or subjects who are usually called informants or respondents through data collection instruments such as interviews and then combines it with data from library materials, especially those related to legal issues. Indonesia based on Law No. 12 of 2011 in conjunction with Law 15 of 2019 has determined a review system and monitoring in law formation, but the best practice from French regarding legislation reviews by independent institutions, called constitutional council and evaluation methods that implement by Australian with the sunset regulation and rescheduling culled methods provides a new perspective on the formation and evaluation in Indonesia, there will be consequences in adopting it either partially or completely that will be discussed in further research.